Las Autopromociones de Telemadrid - Castaño Rivero, Victor J.; Gándara Gil, Luis M.; Martínez González, Fidel; Martínez Martínez, Félix; Salvadores Serrano, Begoña (Cuadernos de Documentación Multimedia, 2018)
Las Autopromociones de Telemadrid